Avaliação histomor fométrica dos efeitos da movimentação dentária induzida sobre molares murinos submetidos à luxação extrusiva em períodos tardios - Lelis, Éverton Ribeiro [UNESP] (2015)
The repair process after dentoalveolar trauma (DT) depends on several factors and complications may arise weeks, months or even years after the injury, it is essential for long-term monitoring. Therefore orthodontic approach teeth related episodes of DT greatest concern and requires careful management. The objective of this study was to evaluate root resorptions on traumatized teeth - extrusive luxation (EL), submitted to induced tooth movement (ITM) after later periods of tissue repair. Eighty young male Wistar rats aged 45 days were used in the present study. The animals were divided into eight groups (n = 10): Group 1 (G1) sacrificed 28 days after, without EL and ITM; Group 2 (G2) subjected to EL and sacrificed 28 days after; Group 3 (G3), 28 days after were submitted to a ITM during 7 days and sacrificed; Group 4 (G4) subjected to EL and, 28 days after, ITM during 7 days and sacrificed. Group 5 (G5) sacrificed 45 days after, without EL and ITM; Group 6 (G6) subjected to EL and sacrificed 45 days after; Group 7 (G7), 45 days after were submitted to a ITM during 7 days and sacrificed; Group 8 (G8) subjected to EL and, 45 days after, ITM during 7 days and sacrificed. The tooth used for the procedures was first upper right molar, luxated using Hollemback 3S and moved mesially by nickel-titanium closed coil (50 cN). After the experimental period, the animals were sacrificed by anesthetic overdose and the right maxilla were removed and processed in longitudinal sections stained with hematoxylin and eosin for histological analysis under light microscopy. Analysis of depth of root resorption by means of scores and analysis of resorptive activity through clastic cell count in contact with the radicular dentin was performed. Kappa test was used for intra-examiner reliability with a 95% confidence interval. Reliability results for...